Drug Consumption in University Students of Cienfuegos Province - Raúl López Fernández; Flavia Linares Tovar; Claudia López Palmero; Rosania Olivera Bolaños; Anais Valladares González (Revista Finlay)
Foundation: in the last decades there has been an increment of the use and abuse of drugs in certain social groups. University students are in a vulnerable period, characterized by high alcohol and tobacco consumption. Objective: to characterize drug consumption in university students of Cienfuegos province. Methods: descriptive correlational study, realized in both universities of Cienfuegos province in 2015. From the total of the third year university students understood as the universe, 87 students, selected by a stratified proportional ramdomized sampling, were applied a survey. Results: cigarette consumption was present in 37.5 % of the student son the University of Medical Sciences and 33.3 % in the Carlos Rafael Rodríguez University. With regards to alcohol and coffee students from the University of Medical Sciences reported 75 and 85.4 % respectively and those of the Carlos Rafael Rodríguez University 53.8 and 69.2 % respectively. Conclusion: the characterization of drug consumption in University students of Cienfuegos province evidenced an increase of tobacco, alcohol and coffee. At comparing both universities the consumption predominated in the University of Medical Sciences.